A Study of Various Parameters, Terminology and Analysis of Deterministic Inventory Control Model - Atma Nand; Vineet Kishore Srivastava; Narottam Singh Chauhan (AG Volumes, 2021)
Present-day is the phase of improved globalization, enhanced information technology and production machineries. Low invests, environmental privileges, upgraded transportation and enhanced communication are altogether essential factors that added competition. Furthermore, companies may face growing supplies from customers on buyer related products, consistent lead periods and customer fulfilment. All these growths focus on central competencies generate a necessity for supply chain management, and support on product growth. These days’ supply chain & Inventory control management have become crucial problems in the triumph of any business, fulfilling the certain demand of a customer is the important objective in this area. For past some decades, diverse theoretic approaches have been implemented to counter these types of problems. Ultimately, when we discuss money, minimizing the loss or maximizing the profit is aye the task. In the present scenario industrial business becoming more and more competitive, study of supply chain theory needs advanced knowledge. SCM popularly known as supply chain management is an emerging executive prototype to conform the instantaneous changes of demand of customer inside the emergent world-wide industrial industry. Study about supply chain theory evolve the satisfaction of customer and it consists all direct and indirect stages of customer needs. The theory of supply chain and its management is a summative study of approaches implanted to enhance the entire operation in such a way that products are produced and dispersed at the correct entity, to the correct destination and on time. A key issue in case of supply chain and its management is Inventory theory and its control. From raw material to finished goods, inventories are most essential portion of system supply chain.